ANALISIS KINERJA PETANI JAHE MENGGUNAKAN STRUCTURAL EQUATION MODELING (Analysis Of Ginger Farmers' Performance Using Structural Equation Modeling - Partial Least Squares In West Manggarai) - AHANG, YOHANES SANDRO; YUSNITA, ERI; SUPARTINI, NONOK (Universitas Mulawarman (University of Mulawarman), 2024)
This research aims to analyze the factors influencing the performance of red ginger farmers in Wae Bangka and Wae Mowol Villages, Lembor District, West Manggarai Regency. Specifically, this study investigates the impact of internal and external factors on farmer performance, as well as the role of entrepreneurial orientation as a mediating variable. The results show that internal and external factors have a positive but insignificant effect on the performance of red ginger farmers. Analysis of the relationships between variables reveals that entrepreneurial orientation as a moderating variable has an influence on farmer performance. Furthermore, it was found that internal factors do not moderate the influence of external factors on farmer performance. This study also reveals the important role of entrepreneurial orientation as a mediator. Entrepreneurial orientation is proven to mediate the influence of internal factors on farmer performance. However, entrepreneurial orientation does not mediate the influence of external factors on the performance of red ginger farmers in the region. This research provides valuable insights into the dynamics affecting the performance of red ginger farmers in Wae Bangka and Wae Mowol Villages, and highlights the importance of developing entrepreneurial orientation in improving farmer performance.